Deformation of Orthodontic Archwires Over Time - Wong E.K.F; Borland D.W; West V.C (Sciendo, 1994)
Most previous studies of archwire deformation over time (hereafter referred to as "time-dependent deformation of orthodontic wires") have been conducted at a constant room temperature. In the clinical situation however, arch wires are exposed to 37°C as well as to periods of temperature increase when hot foods or fluids are ingested. The effects of the latter on time-dependent behaviour are largely unknown. Since the introduction of direct electric resistance heat treatment to superelastic nickel titanium wires, there have been no reports on its effect on time-dependent deformation. This study investigated the effects of repeated temperature increases (70°C) on stainless steel, nickel titanium and beta titanium wires. The wires were deflected by approximately 3 and 5 mm on two jigs for periods of 1 minute, 1,7,14 and 28 days. Permanent deformation was measured optically with a measuring microscope and the amount of time-dependent deformation was calculated. Beta titanium wires demonstrated the greatest amount of time-dependent deformation; followed by non-superelastic nickel titanium, stainless steel, and superelastic nickel titanium. Exposure to repeated temperature (70°C) increases and direct electric resistance heat treatment of superelastic nickel titanium did not affect time-dependent behaviour.